Study the pattern of resistance and the effect of risk factors in some intestinal flora isolated from human - Mohsen Al - Akeidi; Ahmed Hekmat (College of Education for Pure Sciences, 2019)
This study was conducted to study the pattern of antibiotic resistance of beneficial and harmful intestinal bacterial flora Bifidobacterium spp. and Lactobacillus spp. as beneficial bacteria and Escherichia coli and Clostridium spp. as harmful bacteria, as well as the study of the effect of three risk factors (age, sex, feeding on milk and dairy products constantly) to resist these bacterial isolates. Results showed that the percentage of isolating Bifidobacterium spp. and Lactobacillus spp. in young ages (15-30 years old) was (67)% (40)%, respectively, which was more than harmful bacteria and the ratios of beneficial bacteria were greater in young ages compared with ages (50-65 years old) and the resistant of beneficial bacteria to were more than the harmful bacteria in younger ages compared to older subjects, well as that rates of isolation of bacteria reached (54.2, 80)% in females than in males, while ratios of isolation of harmful bacteria reached (70, 62.5)% in males than in females, and that resistance of harmful and beneficial bacteria was the highest in females compared to males, with respect to feeding as a risk factor the ratios isolating bacteria from people who consumes milk and dairy products consistently reached (29, 80)% as in people who didn't (71, 20)%, while the ratios of isolating harmful bacteria was (58, 53)% in people who not feed on milk and derivatives consistently than in people who eat constantly and resist harmful bacteria and decreased in people who consume milk and dairy products constantly compared with persons who not feeding constantly .